Comparison of Clinical and Radiological Outcomes in Patients Undergoing Intramedullary Nailing Versus Plate Fixation for Tibial Shaft Fractures - Dr. Abhishek; Dr. Rahul Bains, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Tibial shaft fractures are common long bone injuries requiring surgical fixation for optimal outcomes. Intramedullary nailing (IMN) and plate fixation (PF) are widely used methods, but comparative clinical and radiological data remain varied. Aim: To compare clinical and radiological outcomes in patients undergoing intramedullary nailing versus plate fixation for tibial shaft fractures. Methods: A prospective observational study of 200 patients with tibial shaft fractures treated with either IMN (n=98) or PF (n=102) was conducted. Demographic, clinical, radiological, and functional data were collected. Outcomes measured included union rates, time to union, functional scores, complications, and radiological alignment. Statistical analyses were performed to compare groups. Results: The IMN group showed a higher union rate (92.9% vs. 86.3%, p=0.090) and significantly shorter mean time to union (18.2 ± 3.9 weeks vs. 20.6 ± 4.6 weeks, p < 0.001). Good functional outcomes were more frequent with IMN (86.7% vs. 75.5%, p=0.032). Infection rates trended lower in IMN (5.1% vs. 11.8%, p=0.052). Anterior knee pain was significantly higher in the IMN group (18.4% vs. 2.0%, p < 0.001). Radiological parameters including malunion and limb length discrepancy were comparable. Conclusion: Intramedullary nailing offers faster union and better functional outcomes with fewer infections but increased anterior knee pain compared to plate fixation. IMN should be preferred for most tibial shaft fractures, with plating reserved for selected cases.